Carbon performance evaluation system and practice analysis for the sustainable enterprises. (6th September 2022) - Zhang, Caiping; Yue, Wenjie; Tan, Deming; Su, Zhenkun
Abstract: Sustainable development has become society's focal point. In this context, China's paper industry needs to be more concerned about a low‐carbon strategy. Therefore, a carbon performance evaluation system must be built to guide the low‐carbon enterprise transformation. Based on the carbon value flow analysis, this study takes JX Paper (a paper‐making enterprise) as an example to construct a carbon performance evaluation system consisting of carbon input, transfer, and output indicators. The quantitative and qualitative index weights were determined through a principal component analysis and an analytical hierarchy process. The overall carbon performance increased from 2012 to 2021, but room remains for improvement. These results show that the performance evaluation system provides a helpful reference for enterprises to identify the key factors affecting carbon emissions and evaluate their carbon performance. Moreover, objective criteria should be developed to improve sustainable enterprise carbon performance and low‐carbon competitiveness.